The notion of Habermas’ ‘public sphere’ and its relevance to interrogations of women’s empowerment and leadership in Muslim contexts - Juan Wang (Faculty of Social Sciences and Humanities, UKM,Bangi, 2010)
In the light of J. Habermas’ notion of the ‘public sphere’, this paper explores how a western concept of the ‘public sphere’ can be applied to the women empowerment notion of a ‘Muslim context’ (WEMC). The following questions are asked and discussed in this paper: Can Habermas’ concept be confined only to a secular way of life? How is a public space to be transformed into a ‘safe space’ given the WEMC approaches to communication, resource and alliance building? If public space is the outcome of WEMC/Alliance work with religious/government officials and community leaders, does this create a ‘safe space’ for women? How does communication take place in a controlled ’political space’ and who is in control? The concept of a ‘public sphere’ acquired philosophical and sociological meanings as a notion of the social order in which there is room for societal debate, and accessible to citizens. Does the nature of authority and leadership in China translate meaningfully into the ‘public sphere’? Conclusion: it is still not easy to define a public sphere within a WEMC context since only with the government sanction does the public space become a safe space. Given the nature of authority and leadership in China, it is difficult to see whether a ‘public sphere’ can be seen as a space in which we negotiate our differences with one another and mobilize around a common purpose; the issue becomes very complex.